2018
DOI: 10.15407/ubj90.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and sensitivity of the new test for serological evaluation of tuberculosis using MPT83-MPT63 fusion antigen

Abstract: the aim of this work was to characterize the experimental test-system based on mPt83-mPt63 fusion antigen with reference commercial diagnostics and investigate the basic characteristics of enzyme-linked immunosorbent assay (ELISA) tests such as specificity and sensitivity. In addition, we investigated the correlation of biochemical and immunological parameters of blood samples of patients with tuberculosis, which was correctly diagnosed by those test-systems. It was shown that the developed test-system match t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The experimental test system "IB-Chem Anti-Mycobacterium tuberculosis" is not inferior to the existing diagnostic serological tests in terms of reliability and informativeness; it meets the basic requirements for the use of ELISA test kits in practice. Previous studies have shown that the sensitivity of this test system was 70% and specifi city was 95.5% [21].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The experimental test system "IB-Chem Anti-Mycobacterium tuberculosis" is not inferior to the existing diagnostic serological tests in terms of reliability and informativeness; it meets the basic requirements for the use of ELISA test kits in practice. Previous studies have shown that the sensitivity of this test system was 70% and specifi city was 95.5% [21].…”
mentioning
confidence: 72%
“…In a previously conducted study, indicators of general specifi city and sensitivity of the newly developed test system "IB-Chem Anti-Mycobacterium tuberculosis" and two analogous commercial test systems for detecting IgG antibodies to M.tuberculosis were analysed (test system #1 (Ukraine), test system #2 (Russia)) [21]. The results showed that both commercial diagnostic kits have the same sensitivity rate at 55% (compared to 70% for "IB-Chem Table 3.…”
Section: Discussionmentioning
confidence: 99%